Financial sector: Proportion of women in top decision-making bodies is increasing more slowly than at the beginning of the decade - equal gender representation is still a long way off - Elke Holst; Katharina Wrohlich (DIW Weekly Report, 2018)
Over the past year, the proportion of women serving on the executive and supervisory boards of the top 100 largest banks in Germany rose slightly to almost nine and 23 percent, respectively. However, growth has come to a halt in the 60 largest insurance companies: on both executive and supervisory boards, the proportion of women has sunk to almost nine and 22 percent, respectively. For over ten years, DIW Berlin has been investigating to what extent women are represented in the top decision-making bodies of banks and insurance companies. A phase of stagnation from 2006 to 2010 was followed by a period of dynamic growth until 2014/2015 before largely returning to a slower phase of development. It seems unlikely that the average development over the past 11 years will continue linearly because most banks or insurance companies do not continue to increase the proportion of women on supervisory boards after reaching the 30 percent target mark. The development could be strengthened by a change in corporate culture. These changes include ambitious goals for more women in top positions and their timely implementation as well as a more modern corporate organization. This way, new role models can be formed and gender stereotypes can be dismantled.
Keywords: G2; J16; J78; L32; M14; M51; 330; board composition; board diversity; boards of directors; central banks; corporate boards; Europe; finance industry; financial sector; female directors; gender gap; gender equality; gender quota; Germany; insurance companies; management; public and private banks; supervisory boards; women CEOs